Cost-per-responder analysis of patients with lenalidomide-refractory multiple myeloma receiving ciltacabtagene autoleucel in CARTITUDE-4 - Hansen, Doris K.; Lu, Xiaoxiao; Puglianini, Omar Castaneda; Sorensen, Sonja; Usmani, Saad Z.; Zhang, Eileen; Huo, Stephen; Zhang, Yan; Qureshi, Zaina P.; Jagannath, Sundar (Frontiers in Immunology, 2024)
Ciltacabtagene autoleucel (cilta-cel) is a chimeric antigen receptor T-cell therapy approved for patients with relapsed/refractory multiple myeloma (RRMM). In the phase 3 trial, CARTITUDE-4 (NCT04181827), cilta-cel demonstrated improved efficacy vs. standard of care (SOC; daratumumab plus pomalidomide and dexamethasone [DPd] or pomalidomide plus bortezomib and dexamethasone [PVd]) with a ≥ complete response (≥CR) rate of 73.1% vs. 21.8%. A cost-per-responder model was developed to assess the value of cilta-cel and SOC (87% DPd and 13% PVd) based on the CARTITUDE-4 trial data from a US mixed payer perspective (76.7% commercial, 23.3% Medicare). The model was developed using progression-free survival (PFS), overall survival (OS), and ≥CR endpoints from CARTITUDE-4 over a period of 25.4 months. Inpatient stays, outpatient visits, drug acquisition, administration, and monitoring costs were included. The base-case model assumed an inpatient setting for each cilta-cel infusion; another scenario included 30% outpatient and 70% inpatient infusions. Costs of managing grade 3-4 adverse events (AEs) and grade 1-4 cytokine release syndrome and neurotoxicity were included. Subsequent therapy costs were incurred after disease progression; terminal care costs were considered upon death events. Outcomes included total cost per treated patient, total cost per complete responder, and cost per month in PFS between cilta-cel and SOC. Costs were adjusted to 2024 US dollars. Total cost per treated patient, total cost per complete responder, and total cost per month in PFS were estimated at 704,641, 963,941, and 30,978 for cilta-cel, respectively, and 840,730, 3,856,559, and 42,520 for SOC over the 25.4-month period. Cost drivers included treatment acquisition costs before progression and subsequent treatment costs (451,318 and 111,637 for cilta-cel; 529,795 and 265,167 for SOC). A scenario analysis in which 30% of patients received an outpatient infusion (assuming the same payer mix) showed a lower cost per complete responder for cilta-cel (956,523) than those with an infusion in the inpatient setting exclusively. This analysis estimated that cost per treated patient, cost per complete responder, and cost per month in PFS for cilta-cel were remarkably lower than for DPd or PVd, highlighting the substantial clinical and economic benefit of cilta-cel for patients with RRMM.